ChemInform Abstract: The Copper‐Catalyzed Synthesis of β‐Trifluoromethylated Acrylonitriles and Trifluoromethyl‐Substituted 2H‐Azirines. Issue 50 (December 2015) - He, Yu‐Tao; Wang, Qiang; Zhao, Jiahui; Liu, Xue‐Yuan; Xu, Peng‐Fei; Liang, Yong‐Min
Abstract: using a novel alkyne difunctionalization reaction